2009
DOI: 10.1093/geronb/gbp075
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Types and Subjective Well-being in Chinese Older Adults

Abstract: The study examined social network types in a sample of 1,005 older Chinese adults in Hong Kong and the networks' relations to subjective well-being. Given the nature of kinship in Chinese society, we broke down social support provision by closeness of blood ties (immediate kin, distant kin, and non-kin). Using K-means cluster analysis, we identified 5 network types: diverse, friend focused, restricted, family focused, and distant family. The latter was characterized by few immediate kin but mostly distant kin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
188
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(210 citation statements)
references
References 32 publications
11
188
4
1
Order By: Relevance
“…[37,38] While evidence suggested that U.S. Chinese older adults primarily rely on adult children for social support, [18] family-focused social networks are most beneficial to the well-being of older adults. [39,40] Our finding is supported by a study indicating that decreased affection to and from children is associated with higher risk of loneliness among older adults. [41] Our finding of the association between perceived filial piety receipt and loneliness is consistent with a prior study in mainland China, in which filial piety was identified as a protective factor against loneliness.…”
supporting
confidence: 82%
“…[37,38] While evidence suggested that U.S. Chinese older adults primarily rely on adult children for social support, [18] family-focused social networks are most beneficial to the well-being of older adults. [39,40] Our finding is supported by a study indicating that decreased affection to and from children is associated with higher risk of loneliness among older adults. [41] Our finding of the association between perceived filial piety receipt and loneliness is consistent with a prior study in mainland China, in which filial piety was identified as a protective factor against loneliness.…”
supporting
confidence: 82%
“…Data were taken from a study of the social networks of community-dwelling Chinese older persons in Hong Kong, which oversampled individuals without the immediate fam-ily (Cheng, Chan, Li, & Leung, 2014;Cheng, Lee, Chan, Leung, & Lee, 2009;Cheng, Li, Leung, & Chan, 2011). Participants were recruited from social service agencies on a voluntary basis from February 2006 to December 2007, who provided informed consent to participate in a study on social networks and health.…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese version of the social convoy question-naire (Cheng, Lee, Chan, Leung, & Lee, 2009;Kahn & Antonucci, 1980) was used to solicit social network infor-mation. Participants were asked to name network members and place them in three concentric circles drawn around a center labeled "me."…”
Section: Social Support From Childrenmentioning
confidence: 99%
“…Considering that the types of networks older adults create are culturally dependent and specific, showing differences between countries and across race, gender, and socioeconomic status (Cheng, Lee, Chan, Leung, & Lee, 2009;Doubova et al, 2010;Fiori et al, 2008;Litwin & Shiovitz-Ezra, 2006), it is important not to prioritize certain relationships over others. This may be critical for marginalized groups.…”
mentioning
confidence: 99%